2022
DOI: 10.7717/peerj-cs.1031
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble of adapted convolutional neural networks (CNN) methods for classifying colon histopathological images

Abstract: Deep convolutional neural networks (CNN) manifest the potential for computer-aided diagnosis systems (CADs) by learning features directly from images rather than using traditional feature extraction methods. Nevertheless, due to the limited sample sizes and heterogeneity in tumor presentation in medical images, CNN models suffer from training issues, including training from scratch, which leads to overfitting. Alternatively, a pre-trained neural network’s transfer learning (TL) is used to derive tumor knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, in [17], article classification accuracy is 95%, and the author achieved the accuracy using texture classification and maximum perimeter. The authors of [19], [20] presented a method for detecting and characterizing cell structure. The study [21]on breast cancer categorized as C3 and C4 on fine needle aspiration cytology aims to correlate with the histopathology examination.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, in [17], article classification accuracy is 95%, and the author achieved the accuracy using texture classification and maximum perimeter. The authors of [19], [20] presented a method for detecting and characterizing cell structure. The study [21]on breast cancer categorized as C3 and C4 on fine needle aspiration cytology aims to correlate with the histopathology examination.…”
Section: Related Workmentioning
confidence: 99%
“…Albashish et al [18] proposed two different types of ensemble learning techniques such as product rule and majority voting. These strategies are intended to categorize colon cancer histopathology images into distinct classifications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent developments showed that deep learning models outperformed traditional features [6,7]. Several deep learning methods, such as supervised learning where models are pre-trained on general images or fine-tuned on histopathological images, have been used to train feature extractors [9][10][11][12][13], and self-supervised learning (SSL), which allows learning from unlabeled images [14][15][16]. However, no studies have reviewed which method is most suitable for CBIR in oral tumors.…”
Section: Introductionmentioning
confidence: 99%